PENYULUHAN TENTANG PEMANFAATAN JUS WORTEL TERHADAP PENURUNAN NYERI DISMENOREA PADA REMAJA PUTRI - Husna Sari; Vitrilina Hutabarat; Erlina Hayati; Septa Dwi Insani (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
Dysmenorrhea is menstrual pain that can cause women's daily activities to be hampered and women's performance to decrease. On average, more than 50% of women experience dysmenorrhea in each country. So far, many have overcome the pain of dysmenorrhea by using analgesic drugs which are not good for long-term health. The pain level of dysmenorrhea should be reduced using traditional medicine with few or no side effects. Carrot juice is one of the non-pharmacological methods that is easy to do. Carrots contain vitamin E and anti-inflammatory effect on Beta carotene and also as an analgesic that can affect the pain of dysmenorrhea in adolescent girls. The purpose of this counseling is to inform young women about the use of carrot juice to reduce dysmenorrhea pain. This counseling was carried out using the method of socialization and direct guidance in making carrot juice. The result of this activity is that young women can know and use traditional plants such as carrots and can apply them directly to reduce dysmenorrhoea pain.